2018
DOI: 10.1186/s12906-018-2109-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of seputhecarpan D, thonningiol and 12 other phytochemicals from African flora towards human carcinoma cells

Abstract: Background: Despite the remarkable progress in cancer therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…Our study corresponds with other studies dealing with these chemicals. For example, in the study by Kuete et al (2018), ß-amyrin produced a selective cytotoxic effect against Caco-2 compared to that on normal cell line HEK293. In another study, extract of Alstonia macrophylla Wall.…”
Section: Discussionmentioning
confidence: 99%
“…Our study corresponds with other studies dealing with these chemicals. For example, in the study by Kuete et al (2018), ß-amyrin produced a selective cytotoxic effect against Caco-2 compared to that on normal cell line HEK293. In another study, extract of Alstonia macrophylla Wall.…”
Section: Discussionmentioning
confidence: 99%
“…Outro estudo descreveu que a curcumina foi capaz de atuar como potente inibidor de NF-kß (fator nuclear kappa ß), podendo ser caracterizado como potente agente anticâncer, uma vez que esse complexo proteico (NF-kß) está relacionado à reposta de estímulos de estresse e sua desregulação tem ligação com o desenvolvimento de tumores 12,76 . Além disso, a curcumina foi associada à parada do ciclo celular na fase G2/S, induzindo apoptose.…”
Section: Discussionunclassified
“…O ácido ursólico, um triterpenoide pentacíclico identificado nas ceras epicuticulares das maçãs e amplamente encontrado nas cascas das frutas e plantas medicinais, foi capaz de induzir apoptose nas células cancerosas do câncer de pele por meio do aumento da concentração de capazes, em especial a caspase número 3 efetora, responsável por clivar substratos, dando sequência à cascata que leva à morte celular 76 . Os resultados encontrados mostraram uma eficácia dose-dependente, o que sugere que a aplicação coadjuvante ao tratamento de câncer deverá ser feita com o composto isolado, com o intuito de potencializar os efeitos da terapia convencional 91 .…”
Section: Discussionunclassified
“…Glyasperin F may regulate cell growth by affecting the activation of MMP1 Glyasperin F is an isoflavone compound, studies have found that Glyasperin F can inhibit the proliferation of lung cancer cells (Ngnintedo et al, 2016;Kuete et al, 2018).…”
Section: Glycyrol May Affect Cell Proliferation and Survival By Regul...mentioning
confidence: 99%